1978
DOI: 10.3146/i0095-3679-5-1-14
|View full text |Cite
|
Sign up to set email alerts
|

Response of Five Peanut Cultivars to Gypsum Fertilization On Soils Varying in Calcium Content1

Abstract: Experiments were conducted to characterize the response to Ca of two recently released peanut (Arachis hypogaea L.) cultivars, ‘Tifrun’ and ‘Early Bunch’ and to compare their response to that obtained from ‘Florunner’, ‘Florigiant’, and ‘NC-Fla 14’. Gypsum (CaSO4•2H2O, approximately 72% CaSO4) was applied at rates of 0 and 1,121 kg/ha in a split plot design using the above cultivars. The experiment was conducted on Fuquay loamy sand low in Ca content and on Greenville sandy loam relatively high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In 1998 at the Wilson County location, all Ca rates except by-product Ca at 560 kg/ha applied at plant decreased disease development up to 50% when compared with the non-treated control ( applied, to 46 and 51%, respectively. Walker and Keisling (1978) reported Ca increased percentage TSMK of five cultivars. Hallock and Allison (1980) reported similar results in Virginia using several different Ca sources.…”
Section: Resultsmentioning
confidence: 97%
“…In 1998 at the Wilson County location, all Ca rates except by-product Ca at 560 kg/ha applied at plant decreased disease development up to 50% when compared with the non-treated control ( applied, to 46 and 51%, respectively. Walker and Keisling (1978) reported Ca increased percentage TSMK of five cultivars. Hallock and Allison (1980) reported similar results in Virginia using several different Ca sources.…”
Section: Resultsmentioning
confidence: 97%
“…Virginia‐type peanut cultivars are characterized by large seed and pods, in comparison with the runner types. Individual seed weight of typical Virginia‐type cultivars range from 0.85 g to 1.2 g, whereas individual seed weight of runner types range from 0.55 g to 0.75 g. Several studies have demonstrated that the large seeded Virginia‐type cultivars require more Ca than the relatively small seeded runner or Spanish types (Cox et al, 1982; Gaines et al, 1989; Middleton et al, 1945; Walker et al, 1976; Walker and Keisling, 1978). The critical soil Ca concentration for optimum pod yield of Virginia types has been reported to be about 560 kg ha −1 , where as, it is about 270 kg ha −1 for runner types (Cox et al, 1982) although there is not broad consensus found in the literature.…”
mentioning
confidence: 99%
“…Soil Ca level needed to produce optimum yield is dependent on seed size. Larger seeded cultivars require higher levels of Ca in the pod zone than smaller seeded cultivars (Gaines et al, 1989;Walker and Keisling, 1978). These studies involved peanut response to gypsum application and noted that larger seeded cultivars, considered Virginia market types, have a positive yield response to gypsum application in soils with Ca levels up to 1559 kg/ha at the 0 to 8 cm depth.…”
Section: Introductionmentioning
confidence: 99%